A RARE PEDIATRIC CASE OF CHRONIC ARSENIC POISONING FROM AYURVEDIC MEDICATION - DHATI RAVI, MANDYAM; BABU, TIRIN; PANACHIYIL, GEORGE MATHEW; SEBASTIAN, JUNY (Asian Journal of Pharmaceutical and Clinical Research, 2020)
Ayurveda is an indigenous system of medicine becoming more popular around the world in recent years. In various Ayurvedic formulations, the arsenical compounds are intentionally added as the main active ingredients or as an auxiliary agent to assist the efficacy of herbal drugs. The chronic arsenic poisoning following the use of Ayurvedic medication is reported rarely in the literature. This report describes a rare pediatric case of chronic arsenic poisoning from Ayurvedic medication in a 15-year-old girl. She was a known case of seizure disorder and was on treatment with Ayurvedic medication for 1 year. The generalized hyperpigmentation and thickening of soles were noticed in the girl 7 months after taking the herbal tablet. The plasma-coupled atomic absorption spectroscopy of herbal tablet was performed in a laboratory and the result showed 4.3 mg of arsenic present in each herbal tablet. The patient was advised to stop the Ayurvedic medication and as an alternate drug, tablet levetiracetam (250 mg, twice a day) was started for the treatment of seizure disorder. During the follow-up, her cutaneous manifestations improved and is doing well.